Guidance facilities and problems in the high schools of San Jose, Nueva Ecija - Bautista, Revelina (Mangaser) 1908- ([Quezon City University of the Philippines], 1953)
This study identifies the facilities for guidance work that are provided in the high schools of San Jose, Nueva Ecija. The study also investigates the adequacy of these facilities, the prevailing types of guidance problems, the ways these guidance problems are being treated and solved and the positive and negative phases of the guidance program.
Bibliography: p. 54.
Thesis (M.Ed.)--University of the Philippines, 1953
Typewritten
Vita
Keywords: Personnel service in education; High schools -- Nueva Ecija -- San Jose